Long Hours and Longings: Australian Children's Views of Fathers' Work and Family Time - Lyndall Strazdins; Jennifer A. Baxter; Jianghong Li (Journal of Marriage and Family, 2017)
Using two waves of paired data from a population sample of 10- to 13-year-old Australian children (5,711 father–child observations), the authors consider how the hours, schedules, intensity, and flexibility of fathers' jobs are associated with children's views about fathers' work and family time. A third of the children studied considered that their father works too much, one eighth wished that he did not work at all, and one third wanted more time with him or did not enjoy time together. Logistic regression modeling revealed that working on weekends, being time pressured, being unable to vary start and stop times, and working long hours generated negative views in children about fathers' jobs and time together. The time dilemmas generated by fathers' work devotions and demands are salient to and subjectively shared by their children.
Keywords: 330; child well-being; families and work; fathers; time use; work–family balance; work hours